Drug-related problems and pharmacist interventions in a cohort of patients with asthma and chronic obstructive pulmonary disease - RABUŞ, ŞULE (W B SAUNDERS CO LTD, 2016)
Background: Asthma and chronic obstructive pulmonary disease are preventable and treatable chronic airway diseases with high incidence and prevalence. Pharmacists and clinical pharmacy based pharmaceutical care services have positive impact on therapy outcomes. Objective: The aim of this study is to describe drug related problems in a cohort of patients with asthma and chronic obstructive pulmonary disease and to assess interventions provided by the pharmacist to address these problems in a community pharmacy. Method: Study population consisted of patients with asthma and chronic obstructive pulmonary disease older than 18 years who visited the study pharmacy during the pre-determined six-month period. The patients whose disease control states were not fully controlled were included in our study for further steps. On the first interview, present and potential drug related problems were addressed, interventions were provided. Follow-up interviews were held one month and two months later than the first interview. Results: For the 44 patients with asthma, 59 drug-related problems and 134 causes for these problems were identified. Eighty-four interventions were made to resolve the problems; and 54.2% of the problems were resolved. For the 37 patients with chronic obstructive pulmonary disease, 60 drug-related problems and 128 causes for these problems were identified. Ninety-five interventions were made to resolve the problems; and 63.3% of the problems were resolved. Conclusion: Pharmacists taking part in therapy and management of asthma and chronic obstructive pulmonary disease can help patients be more educated about their disease and medications; and improve disease control and therapy outcomes. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Asthma; COPD; Community pharmacy; Drug-related problems; Pharmaceutical care; IMPROVE INHALATION TECHNIQUE; SMOKING-CESSATION; COMMUNITY PHARMACISTS; INHALER TECHNIQUE; LED INTERVENTION; THERAPY; PROGRAM; COPD; CARE; ADHERENCE